2022
DOI: 10.3389/fsufs.2022.995224
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of weed and insect populations by living cover crop mulches in organic squash production

Abstract: Living mulch systems can provide multiple agronomic and ecosystem benefits, including reducing erosion and decreasing weed and pest pressure. However, inconsistent yields and lack of best practices for weed and pest management have contributed to their lack of adoption by farmers. In 2018 and 2019, living mulch practices for organic zucchini (Cucurbita pepo L.) production were assessed in Wisconsin on certified organic land. Living mulches of Dutch white clover (Trifolium repens), annual ryegrass (Lolium multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…These results are aligned with previous work in plasticulture acorn squash (Cucurbita pepo cv. Table Ace) production (Nelson and Gleason, 2018), but contrast with results from Bruce et al (2022) where researchers found that clover/ryegrass and ryegrass living mulch between plastic mulched beds reduced zucchini (Cucurbita pepo cv. Dunja F1) yields compared to a cultivated and straw mulch control.…”
Section: Cash Crop Performancementioning
confidence: 63%
See 1 more Smart Citation
“…These results are aligned with previous work in plasticulture acorn squash (Cucurbita pepo cv. Table Ace) production (Nelson and Gleason, 2018), but contrast with results from Bruce et al (2022) where researchers found that clover/ryegrass and ryegrass living mulch between plastic mulched beds reduced zucchini (Cucurbita pepo cv. Dunja F1) yields compared to a cultivated and straw mulch control.…”
Section: Cash Crop Performancementioning
confidence: 63%
“…Previous research investigating the use of living mulches between plastic mulch beds have focused on comparisons against a narrow set of common grower practices. For example, comparing living mulch treatments to cultivation (Reiners and Wickerhauser, 1995;Rice et al, 2004;Butler, 2012;Reid and Klotzbach, 2013;Ivy et al, 2014;Warren et al, 2015) or straw/dead mulches (Law et al, 2006;Nelson and Gleason, 2018), but few have compared these practices against one another within the same experiment (Law et al, 2006;Bruce et al, 2022). Furthermore, mowing ambient weeds between plastic mulch beds is a common grower practice, but has gone relatively uninvestigated in the literature (Law et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Living mulches are often investigated for their ability to provide ecosystem services such as weed suppression and/or enhancing populations of arthropod natural enemies (Manandhar & Wright 2016;Kahl et al 2019;Bhaskar et al 2021;Bruce et al 2022;Yurchak et al 2023). Notwithstanding, flowering living mulches may also enhance floral visitor and potentially pollinator abundance through the provision of food.…”
Section: Butterfliesmentioning
confidence: 99%
“…However, living mulches may be a viable option for weed control in the furrows because the seed is relatively inexpensive. These mulches can also potentially enhance soil health by incorporating organic matter and limiting erosion (Bhaskar et al 2021;Brown 2017;Bruce et al 2022). Living mulches have been used in cucurbit production under rowcovers (Bruce et al 2022;Nair et al 2014).…”
mentioning
confidence: 99%
“…These mulches can also potentially enhance soil health by incorporating organic matter and limiting erosion (Bhaskar et al 2021;Brown 2017;Bruce et al 2022). Living mulches have been used in cucurbit production under rowcovers (Bruce et al 2022;Nair et al 2014). In mesotunnels during an Iowa organic 'Athena' muskmelon trial, however, both seeding red clover (Trifolium pratense) alone and a mixture of annual ryegrass (Lolium multiflorum) plus red clover were ineffective because these mulches were outcompeted by weeds (Nelson 2019).…”
mentioning
confidence: 99%